Once-Daily Dosing of Aminoglycosides - William A Craig (Canadian Journal of Infectious Diseases)
OBJECTIVE: To review the pharmacodynamic rationale for once-daily dosing of aminoglycosides and to summarize thee results of comparative trials in animals and humans. DATA SOURCES: Published articles on the pharmacodynamics of aminoglycosides and those comparing the therapeutic efficacy and toxicity of once-daily administration will more frequent closing regimens. DATA SELECTION: Fourteen randomized studies in infected patients that compared the efficacy and toxicity of once-daily aminoglycoside dosing with twice- or thrice-daily dosing regimens were available for review. Ten studies comparing the efficacy and toxicity of different an1inoglycoside dosing regimens in animal models were also reviewed . DATA EXTRACTION: Frequency of clinical response, nephrotoxicity and ototoxicity with each dosing regimen were compared graphically and by x2 for statistical significance (P<0.05). DATA SYNTHESIS: Once-daily dosing was consistently less toxic than more frequent dosing in animals. When human pharmacokinetics were simulated in animals, efficacy of once-daily dosing was similar or enhanced over more frequent dosing regimens. Once-daily dosing in patients, compared with twice- or thrice-daily administration, was statistically more effective in two studies, less nephrotoxic in six studies, and less ototoxic in one study. Similar efficacy and toxicity were observed in all the oilier studies. CONCLUSIONS: Once-daily dosing of aminoglycosides has the potential to enhance efficacy, reduce toxicity and lower administration costs for this drug class. The once-daily dosing regimen deserves serious consideration for routine use of the aminoglycosides.